How do you simplify (x + 2)(x - 2)?

1 Answer
May 7, 2018

(x+2)(x-2)=x^2-4

Explanation:

Use the distributive property to multiply both terms in the first set of parenthesis by the terms in the second set:
First the x:
x*x=x^2.
x*(-2)=-2x.
Now the 2:
2*x=2x.
2*(-2)=-4.
We came up with four terms: x^2-2x+2x-4.
Simplify the expression by adding the middle terms, and we get just x^2-4.

This is a special kind of binomial (a binomial is an expression with two terms) called a difference of squares. Since (x+2)&(x-2) are the same except for the sign in between, the answer is just the first term squared (x^2) minus the second term squared
-(2^2)=-4.
Here's more about difference of squares: https://www.mathsisfun.com/definitions/difference-of-squares.html